Endoplasmic reticulum stress disrupts signaling via altered processing of transmembrane receptors - Bosakova, Michaela; Abraham, Sara P; Wachtell, Davis; Zieba, Jennifer T; Kot, Alexander; Nita, Alexandru; Czyrek, Aleksandra Anna; Koudelka, Adolf; Ursachi, Vlad-Constantin; Feketova, Zuzana; Rico-Llanos, Gustavo; Svozilova, Katerina; et al. (Cell communication and signaling, 2025)
Cell communication systems based on polypeptide ligands use transmembrane receptors to transmit signals across the plasma membrane. In their biogenesis, receptors depend on the endoplasmic reticulum (ER)-Golgi system for folding, maturation, transport and localization to the cell surface. ER stress, caused by protein overproduction and misfolding, is a well-known pathology in neurodegeneration, cancer and numerous other diseases. How ER stress affects cell communication via transmembrane receptors is largely unknown. In disease models of multiple myeloma, chronic lymphocytic leukemia and osteogenesis imperfecta, we show that ER stress leads to loss of the mature transmembrane receptors FGFR3, ROR1, FGFR1, LRP6, FZD5 and PTH1R at the cell surface, resulting in impaired downstream signaling. This is caused by downregulation of receptor production and increased intracellular retention of immature receptor forms. Reduction of ER stress by treatment of cells with the chemical chaperone tauroursodeoxycholic acid or by expression of the chaperone protein BiP resulted in restoration of receptor maturation and signaling. We show a previously unappreciated pathological effect of ER stress; impaired cellular communication due to altered receptor processing. Our findings have implications for disease mechanisms related to ER stress and are particularly important when receptor-based pharmacological approaches are used for treatment.
Keywords: Receptors, Cell Surface; stres endoplazmatického retikula; signální transdukce; Endoplasmic Reticulum Stress; Endoplasmic Reticulum Chaperone BiP; Animals; nádorové buněčné linie; lidé; Taurochenodeoxycholic Acid; Signal Transduction; chaperon endoplazmatického retikula BiP; Cell Line, Tumor; receptory buněčného povrchu; zvířata; Humans; kyselina taurochenodeoxycholová